Performing ethics through film style : Levinas with the Dardenne Brothers, Barbet Schroeder and Paul Schrader - Lamberti, Edward (Edinburgh University Press, 2020)
Proposing a relationship between Levinasian ethics and film style, and bringing it into a productive dialogue with theories of performativity, this book explores this influence through three directorial bodies of work: those of Barbet Schroeder, Paul Schrader and the Dardenne Brothers.